Protein Carbonyl, But Not Malondialdehyde, Is Associated With ICU Mortality in Patients With Septic Shock - Costa, Nara Aline [UNESP] (2019)
Background: The objective of our study was to evaluate the association of serum malondialdehyde (MDA) and protein carbonyl concentration with intensive care unit (ICU) mortality in patients with septic shock. Methods: We prospectively evaluated 175 patients aged over 18 years with septic shock upon ICU admission. However, 16 patients were excluded. Thus, 159 patients were enrolled in the study. In addition, we evaluated 16 control patients. At the time of the patients’ enrollment, demographic information was recorded. Blood samples were taken within the first 24 hours of the patient’s admission to determine serum MDA and protein carbonyl concentrations. Results: The mean age was 67.3 ± 15.9 years, 44% were males, and the ICU mortality rate was 67.9%. Median MDA concentration was 1.53 (0.83-2.22) µmol/L, and median protein carbonyl concentration was 24.0 (12.7-32.8) nmol/mL. Patients who died during ICU stay had higher protein carbonyl concentration. However, there was no difference in MDA levels between these patients. Receiver operating characteristic curve analysis showed that higher levels of protein carbonyl were associated with ICU mortality (area under the curve: 0.955; 95% confidence interval [CI]: 0.918-0.992; P <.001) at the cutoff of >22.83 nmol/mL (sensibility: 80.4% and specificity: 98.1%). In the logistic regression models, protein carbonyl concentrations (odds ratio [OR]: 1.424; 95% CI: 1.268-1.600; P <.001), but not MDA concentrations (OR: 1.087; 95% CI: 0.805-1.467; P =.59), were associated with ICU mortality when adjusted for age, gender, and Acute Physiology and Chronic Health Evaluation (APACHE) II score; and when adjusted by APACHE II score, lactate, and urea; protein carbonyl concentrations (OR: 1.394; 95% CI: 1.242-1.564; P <.001); and MDA (OR: 1.054; 95% CI: 0.776-1.432; P =.73). Conclusion: In conclusion, protein carbonyl, but not MDA, concentration is associated with ICU mortality in patients with septic shock.